Detección de especies de Aeromonas en heces de niños asintomáticos - Piñero M; Quinteros A; Tricase M; Paz A; Fuenmayor A (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2001)
Abstract: Diarrheic diseases constitute a world problem of public health, specially in developing countries, such as Venezuela where gastroenteritis has an important place as a cause of infant mortality and morbidity. Finding bacteria of the genus Aeromonas among the main etiological agents. Despite that, the clinical meaning of their isolation is not completely established, due to the existence of healthy carriers. The purpose of this investigation was to detect bacterial species of the genus Aeromonas in fecal samples in apparently healthy children, to clarify the existence of asymptomatic carriers in our medium and to contribute to elucidating the clinical importance of its isolation in patients with gastroenteritis. This investigation took place during the period September- December 1999, and samples from122 children of both sex groups were analyzed, with ages between 3 months and six years, enrolled in 16 kindergartens in the Chiquinquira prefecture of Maracaibo Municipality. The analysis of the samples for the detection of pheno-species of the genus Aeromonas was done using the conventional diagnostic methodology based on biochemical tests. In the analyzed samples 27,87% (34/122) were positive. The species of Aeromonas isolated by order of frequency were: A. caviae (52,78%), A. jandaei (19,44%), A. veronii biovar sobria (13,89%), A. hydrophila (11,11%) and A. trota (2,78%). In the majority of cases (94.1%) only one species per sample was isolated. The distribution of Aeromonas by age and sex group was not statistically significant (p>0,05). The results obtained in this investigation show the existence of a considerable number of a-symptomatic carriers of Aeromonas in the children studied, which makes it essential to carry out more research that contribute to establish the importance of their detection in patients with diarrhea. Resumen: Las enfermedades diarreicas constituyen un problema de salud pública a nivel mundial, especialmente en los países en vías de desarrollo, como Venezuela donde representan ...